DEVELOPMENT OF EXTRACURRICULAR PHYSICAL CULTURE AND SPORTS ACTIVITIES AT THE UNIVERSITY, TAKING INTO ACCOUNT MODERN CHALLENGES - Lubysheva L.I. ,; Pashchenko L.G. , (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify current trends and determine the vector of development of extracurricular physical culture and sports activities of university students, taking into account the social challenges of modern society. Methods and structure of the study. Scientific work included: theoretical analysis of factors influencing the development of extracurricular physical culture and sports activities of students; sociological survey of 726 university students; designing a patriotic sports event "Army Games" and its implementation on the basis of Nizhnevartovsk State University. Results and conclusions. Among the factors influencing the choice of forms and content of extracurricular physical culture and sports activities of student youth are: the orientation of the modern system of higher education to the individual needs of an individual in obtaining knowledge and developing competencies; social order of the state to increase the patriotic potential of students; taking into account the preferences of young men and women in the choice of mass physical culture and sports events; taking into account the psychological characteristics of the modern generation. The experience of developing and implementing a physical culture and sports project of a patriotic orientation "Army Games", which includes 70% of tasks of a practical and 30% of a theoretical orientation, showed the possibility of creating conditions for the integration of the individual abilities of individual participants to achieve collective goals in a team interaction, contributing to an increase in the indicator of student involvement in extracurricular physical culture and sports activities.